Nurses' Experiences of Communicating With Families in Municipal Home Health Care - Elisabeth Bruce; Susanna Pusa; Karin Sundin (Nursing Open)
ABSTRACT Aim To illuminate nurses' experiences of communicating with families in home health care. Design A qualitative inductive approach. Background An increasing number of ageing and sick people are being granted home health care. Nurses' duties involve caring for both patients and their families, which includes the important task of meeting and talking with them. Methods Fourteen registered nurses working in home health care in Sweden participated in individual narrative semistructured interviews. The interviews were analysed with content analysis. To make sure all components of the study were clear, the Standards for Reporting Qualitative Research checklist was used as a guide. Result Communication with families was viewed as a crucial action for building rapport to facilitate the involvement and support of families in difficult situations. The nurses highlighted the struggles they sometimes faced in communication when they found it difficult to reach the family. When the communication was supportive for the family, the nurses felt that they were empowering the family members to empower themselves. Conclusion This study highlights the vital role of communication in home health care nursing. Effective communication fosters trust and enables nurses to meet family needs. Implications for the Profession Effective communication between nurses and families in home health care is crucial from a health care perspective. Building reciprocal relationships fosters trust, enabling nurses to efficiently identify and address family needs and enhancing the quality of care. Patient or Public Contribution No patient or public contribution.